2008
DOI: 10.1177/147323000803600406
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Over-expression of Glial Cell-derived Neurotrophic Factor and Its RET Receptor with Progression and Prognosis of Human Pancreatic Cancer

Abstract: We used immunohistochemical staining to assess protein over-expression of glial cell-derived neurotrophic factor (GDNF) and its RET receptor tyrosine kinase in patients with pancreatic cancer and benign pancreatic neoplasm, and assessed correlations with clinicopathological features and prognosis. Surgically resected pancreatic cancer patients (40/58, 68.9%) showed positive GDNF immunostaining, a significantly higher frequency than in patients with benign pancreatic tumour (3/11, 27.3%). Intrapancreatic neural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 20 publications
0
57
0
Order By: Relevance
“…Patients with a surgically resected pancreatic cancer showed a significantly higher frequency of positive glial cell line-derived neurotrophic factor (GDNF) immunostaining, and the intrapancreatic neural invasion by cancer cells was significantly related to the overexpression of GDNF (Zeng et al 2008). Importantly, a strongly positive expression of GDNF was significantly more frequent than lesser grades of GDNF expression in patients with pancreatic cancer (Zeng et al 2008).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Patients with a surgically resected pancreatic cancer showed a significantly higher frequency of positive glial cell line-derived neurotrophic factor (GDNF) immunostaining, and the intrapancreatic neural invasion by cancer cells was significantly related to the overexpression of GDNF (Zeng et al 2008). Importantly, a strongly positive expression of GDNF was significantly more frequent than lesser grades of GDNF expression in patients with pancreatic cancer (Zeng et al 2008).…”
Section: Introductionmentioning
confidence: 93%
“…Importantly, a recent report has shown that the severity of the neural invasion in rectal adenocarcinoma is an important factor in a scoring system to assess the prognostic value, showing high correlation with localization and severity (Ceyhan et al 2010). Patients with a surgically resected pancreatic cancer showed a significantly higher frequency of positive glial cell line-derived neurotrophic factor (GDNF) immunostaining, and the intrapancreatic neural invasion by cancer cells was significantly related to the overexpression of GDNF (Zeng et al 2008). Importantly, a strongly positive expression of GDNF was significantly more frequent than lesser grades of GDNF expression in patients with pancreatic cancer (Zeng et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…RET oncogenic mutations contribute to cell transformation in medullary thyroid cancer (MTC) 2 (1). MTC occurs in sporadic (75%) or hereditary (25%) forms with three clinical subtypes: multiple endocrine neoplasia types 2A and 2B and familial MTC.…”
Section: Dent Inactivation Of Atf4 During the Pathogenesis Of Medullamentioning
confidence: 99%
“…Furthermore, RET overexpression has been observed in pancreatic cancer (2), melanoma (3), and leukemia (4). RET copy number gains, mutations, and rearrangements have been observed in breast cancer (5).…”
Section: Dent Inactivation Of Atf4 During the Pathogenesis Of Medullamentioning
confidence: 99%
“…In another pancreatic cancer patient, an intronic L1 in the GDNF gene was also present in both the primary cancer and its metastasis. GDNF is a glial cell line-derived neurotrophic factor and a ligand of RET, which has been suggested to participate in pancreatic cancer progression and invasion (Zeng et al 2008). Intronic L1 insertions were likewise found in stomach tumors in the cancer driver candidate genes KLF12 (Kruppel-like factor 12), a known player in gastric cancer progression (Nakamura et al 2009), and in CTNND2, which encodes for catenin delta 2.…”
Section: Insertions In Known or Candidate Cancer Driver Genesmentioning
confidence: 99%